Doubtful democrats: Democracy in Britain since 1800. Issue 2 (May 2019) - Saunders, Robert
Over the 'long' 19th century, British politics underwent a quiet revolution: a revolution, not in its governing institutions, but in the ideas that underpinned them. In little more than a century, the idea of 'democracy'—once a term of abuse, from which even radical politicians sought to disassociate themselves—established itself as the civic religion of British politics: the one authority against which there could be no court of appeal. Like other religions, democracy spawned a variety of sects and denominations, each of which sought to defend it against false democratic creeds: ranging from 'social democracy' and 'industrial democracy' to 'Tory democracy', 'the property-owning democracy', and 'the democracy of the market'. The result, paradoxically, was to establish democracy both as the universal principle of British politics and as its central battlefield: an idea to which all paid tribute, but which seemed permanently under siege. This article explores the peculiar voyage of British democratic thought over the 19th and 20th centuries, focusing on its usage as an instrument of political warfare. The first section charts its emergence as the most potent challenge to the dominant narratives of the early-19th century: Whig constitutionalism and 'reform'. A second section then charts the absorption of democracy into the core narratives of British political thought, while exploring the very different ends to which its authority could be put. A final section identifies three narrative battlegrounds for democracy in the 19th century, opening up fault lines that continue to structure British politics in the present.